Evaluation of Agricultural Work Environment with Ergonomic Checkpoints in Demangan, Siman, Ponorogo - Ratih Andhika Akbar Rahma; Fahri Cahyo Satria; Aisy Rahmania; Rindang Diannita (Jurnal Ilmiah Teknik Industri, 2022)
An ergonomic checkpoint is a method for evaluating the current work environment and implementing a more suitable work environment. When workers do work activities, the work environment is a critical component. Ergonomics is described as studying human factors in the workplace, including anatomy, physiology, psychology, engineering, management, and design. Based on preliminary observations, several activities allow potential hazards to arise, such as farmers’ lack of understanding of Personal Protective Equipment (PPE) when spraying pesticides and farmers’ use of t-shirts as a mask. Farmers repeated movements with a bent body position when planting rice seeds, which can cause potential health problems such as musculoskeletal. Using descriptive observational research, this study tries to objectively establish the conditions of the work environment concerning the circumstances. The Ergonomic Checkpoints method was used for data collecting. The results of the work environment assessment using the Ergonomic Checkpoints method in agriculture in Demangan Village revealed that five aspects that required corrective action, consisting of materials storage, and handling, had two points of incompatibility, machine safety had one moment of incompatibility, premises/workspace had one moment of incompatibility, and welfare facility had one moment of mismatch. Farmers in Demangan village should use Ergonomic Checkpoints to pay attention to the work environment in keeping with agricultural standards.